Step 1: Differentiate \( x \) with respect to \( \theta \).
Given:
\[
x = a(1 - \cos\theta)
\]
Differentiate both sides with respect to \( \theta \):
\[
\frac{dx}{d\theta} = a \sin\theta.
\]
Step 2: Differentiate \( y \) with respect to \( \theta \).
Given:
\[
y = a(\theta + \sin\theta)
\]
Differentiate both sides with respect to \( \theta \):
\[
\frac{dy}{d\theta} = a(1 + \cos\theta).
\]
Step 3: Compute \( \frac{dy}{dx} \).
Using the chain rule:
\[
\frac{dy}{dx} = \frac{\frac{dy}{d\theta}}{\frac{dx}{d\theta}} = \frac{a(1 + \cos\theta)}{a \sin\theta}.
\]
Simplify:
\[
\frac{dy}{dx} = \frac{1 + \cos\theta}{\sin\theta}.
\]
Using the identity:
\[
1 + \cos\theta = 2\cos^2 \frac{\theta}{2},
\]
and
\[
\sin\theta = 2\sin\frac{\theta}{2} \cos\frac{\theta}{2},
\]
we get:
\[
\frac{dy}{dx} = \frac{2\cos^2\frac{\theta}{2}}{2\sin\frac{\theta}{2} \cos\frac{\theta}{2}}.
\]
Canceling common terms:
\[
\frac{dy}{dx} = \frac{\cos\frac{\theta}{2}}{\sin\frac{\theta}{2}} = \cot\frac{\theta}{2}.
\]
Conclusion: The correct answer is \( \mathbf{\frac{\cot\theta}{2}} \).